Psycho-social determinants of employee strike propensity among labor union members in an Indian context - Jose, Amal Tom; Jayakumar, K.N.; George, Jovita Sherin (Faculty of Social and Political Science, Universitas Airlangga, 2025)
Understanding the psychological and relational factors that influence strike propensity among unionized employees is crucial for effective labor management. This study examined whether personality traits, employee-employer relationships, and organizational trust influence strike propensity among labor union members affiliated with different political parties (INTUC, BMS, and CITU) in Kerala, India. This study uses a quantitative method, with a cross-sectional survey and was conducted with 505 unionized employees. Strike propensity was significantly positively correlated with extraversion, openness to experience, agreeableness, and co-worker relationships. Significant negative correlations were observed with conscientiousness, neuroticism, employee-supervisor relationships, and employee-organization relationships. Younger adults demonstrated significantly higher strike propensity, compared to middle-aged adults. Multiple regression analysis revealed that openness to experience, extraversion, and supervisor relationships collectively explained 26% of the variance in employee strike propensity (R² = 0.26). Personality traits and workplace relationships significantly influence strike propensity among unionized employees. This study concluded that organizations can potentially reduce strike likelihood by focusing on supervisor-employee relationships and considering personality factors in labor management strategies.